Qualitative analysis of blood from patients engaging in deliberate self‐harm: Differences between prescribed and detected drugs - Masato Masuda; Brian Waters; Leo Gotoh; Yoshihiko Nakamura; Yoshifumi Kato; Shigeki Nabeshima; Shin‐ichi Kubo; Nobuaki Eto; Hiroaki Kawasaki (Wiley, 2024)
Abstract Background While drugs are sometimes taken during deliberate self‐harm (DSH), no study has attempted to analyze drugs in the blood of DSH patients and compare them with prescribed medications or other drugs. In this study, drugs were analyzed from the blood of DSH patients, and the detected, prescribed, and suspected drugs were documented. Methods Patients who practiced DSH and were transferred to the emergency sites of Fukuoka University Hospital between April 2021 and September 2022 participated in the study. Psychiatrists assessed information such as the history of psychiatric treatment and recent methods of DSH, as well as prescribed drugs within 1 month of presenting to the hospital. Blood samples were analyzed using LC-MS/MS. Participants were divided into groups according to whether or not they were prescribed psychotropics within 1 month. Results Fifty‐five patients were enrolled in the study. Forty had been prescribed psychotropics within 1 month of hospital admission. However, non‐prescribed drugs (NPD) were detected in 42 of the 55 participants (76%). The detection of NPD was significantly high among patients with overdose of medications and OTC drugs (p = 0.036), but NPD were also detected in patients who engaged in other methods (n = 14), and in patients without prescribed medication (n = 10). Discussion This is the first study focused on the drug analysis of blood from patients engaging in DSH. Approximately 80% of the DSH patients in this study had taken NPD, revealing a large discrepancy between prescribed medications and those detected in the blood.